The biology of human longevity : inflammation, nutrition, and aging in the evolution of life spans - Finch, Caleb (Burlington, MA : Academic Press, 2007)
The Biology of Human Longevity: Inflammation, Nutrition, and Aging in the Evolution of Lifespans synthesizes several decades of top research, and expands a number of existing major theories, including the Barker theory of fetal origins of adult disease to consider the role of inflammation and Harmon's free radical theory of aging to include inflammatory damage. Future increases in lifespan are challenged by the obesity epidemic and spreading global infections that may reverse the gains made in lowering inflammatory exposure.--BOOK JACKET.
1. INFLAMMATION AND OXIDATION IN AGING AND CHRONIC DISEASES. 1.1. Overview ; 1.2. Experimental models for aging ; 1.3. Outline of inflammation ; 1.4. Bystander damage and dependent variables in senescence ; 1.5 Arterial aging and atherosclerosis ; 1.6. Alzheimer disease and vascular-related dementias ; 1.7. Inflammation in obesity ; 1.8. Processes of normal aging in the absence of specific diseases ; 1.9. Summary -- 2. INFECTIONS, INFLAMMOGENS, AND DRUGS. 2.1. Introduction ; 2.2. Vascular disease ; 2.3. Infections from the central tube : Metchnikoff revisited ; 2.4. Aerosols and dietary inflammogens ; 2.5. Infections, inflammation, and life span ; 2.6. Are infections a cause of obesity? ; 2.7. Inflammation, dementia, and cognitive decline ; 2.8. Immunosenescence and stem cells ; 2.9. Cancer, infection, and inflammation ; 2.10. Pharmacopleiotropies in vascular disease, dementia, and cancer ; 2.11. Summary -- 3. ENERGY BALANCE, INFLAMMATION, AND AGING. 3.1. Introduction ; 3.2. Diet restriction and aging ; 3.3. Energy sensing in diet restriction and satiety ; 3.4. Exercise, cardiovascular health, and longevity ; 3.5. Diet, exercise, and neurodegeneration ; 3.6. Laboratory rodents as models for the 'couch potato' ; 3.7. Energy balance in the life history ; 3.8. Summary -- 4. NUTRITION AND INFECTION IN THE DEVELOPMENTAL INFLUENCES ON AGING. 4.1. Introduction ; 4.2. Synopsis of the fetal origins theory ; 4.3. The Barker studies of infections and vascular disease ; 4.4. Size, health, and longevity ; 4.5. Infection and undernutrition on birthweight and later disease ; 4.6. Infection and nutrition in postnatal development and later disease ; 4.7. Famine ; 4.8. Maternal physiology, fetal growth, and later chronic disease ; 4.9. Growth in adaptive responses to the environment ; 4.10. Genomics of fetal growth regulation ; 4.11. Summary -- 5. GENETICS. 5.1. Introduction ; 5.2. Sources of individual variations in aging and life span ; 5.3. Sex differences in longevity ; 5.4. Metabolism and host-defense in worm and fly ; 5.5. The worm ; 5.6. Fly ; 5.7. Mammals ; 5.8. Summary -- 6. THE HUMAN LIFE SPAN : PRESENT, PAST, AND FUTURE. 6.1. Introduction ; 6.2. From great ape to human ; 6.3. Four major shifts in human life history from genetic and cultural evolution ; 6.4. The instability of life spans ; 6.5. Summary of chapters 1-6 : mechanisms in aging and life history evolution.
Includes bibliographical references (p. 417-599) and indexes.
Keywords: Aging; Inflammation; Longevity; Nutritional Physiological Phenomena